2002
DOI: 10.1021/es0258632
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal Fractionation of Polybrominated Diphenyl Ethers and Polychlorinated Biphenyls in Frogs (Rana temporaria)

Abstract: The flame retardant polybrominated diphenyl ethers (PBDEs) have become ubiquitous environmental pollutants. The environmental distribution of PBDEs is much less studied than that of the polychlorinated biphenyls (PCBs). To compare the environmental fate of the PCBs with their partial substitute, the PBDEs, common frogs (Rana temporaria)were collected along a approximately 1,500-km-long latitudinal gradient of the Scandinavian Peninsula and their livers analyzed for PCBs and PBDEs. Mean concentrations of total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 42 publications
6
33
3
Order By: Relevance
“…Levels of BDEs 47 and 99 in these frogs were 2-10 times higher than those reported in frog Rana temporaria collected from Sweden (Ter Schure et al, 2002), the only available data on PBDE levels in wild frogs for comparison.…”
Section: Reported Pbde Levels In Frogcontrasting
confidence: 59%
“…Levels of BDEs 47 and 99 in these frogs were 2-10 times higher than those reported in frog Rana temporaria collected from Sweden (Ter Schure et al, 2002), the only available data on PBDE levels in wild frogs for comparison.…”
Section: Reported Pbde Levels In Frogcontrasting
confidence: 59%
“…The PBDE burden in tadpoles exposed to 1 ng/L DE-83R reached 11.04 ng/g ww, while it reached 128.09 ng/g ww in 10 ng/L DE-83R treatment group. In consistence with our study, Ter Schure et al (2002) reported that PBDEs burden in some wild amphibians exceed 100 ng/g ww. Therefore, the results from current study demonstrated that DE-83R at close to environmentally relevant concentrations caused thyroid disruption in X. laevis tadpoles.…”
Section: Discussionsupporting
confidence: 91%
“…Tadpole body burden concentrations of SPBDEs in the present study are representative of concentrations found in sediments and fishes throughout the world, including the Great Lakes, as well as invertebrates from the North Sea [13,14,30]. In Scandinavian frog livers, BDE-47 and -99 reached levels of 0.12 and 0.18 ng/g wet weight, respectively [31], but have not been measured in North America where biota PBDE levels are generally an order of magnitude higher than in Europe [14].…”
Section: Diet and Tissue Levels Of Pbdesmentioning
confidence: 57%